Formulation, evaluation and optimization of ziprasidone hydrochloride capsules - BHUSHAN KUMAR, SHASHI; BUNDELA, MS. RAGINI; SARAF, DR. SURENDRA; SHUKLA, DR. KARUNAKAR SHUKLA (International Journal of Multidisciplinary Research and Studies, 2023)
This research focuses on the development, evaluation, and optimization of Ziprasidone Hydrochloride (ZH) capsules, a potent antipsychotic used in managing psychiatric disorders. The process includes formulation design, evaluation of quality attributes, and optimization to improve drug delivery performance. The formulation stage involves selecting appropriate excipients and determining optimal ratios, while the evaluation phase involves rigorous analysis of parameters like weight variation, content uniformity, hardness, disintegration time, and dissolution profiles. The optimization phase uses statistical tools and experimental design methodologies to identify optimal formulation parameters.